Interannual Modulation of Kuroshio in the East China Sea Over the Past Three Decades - Jo, SeongHyun; Moon, Jae-Hong; Kim, Taekyun; Song, Yuhe Tony; Cha, Hyeonsoo (Frontiers in Marine Science, 2022)
Previous studies have suggested that westward-migrating mesoscale eddies are a dominant factor that modulate the interannual Kuroshio intensity in the East China Sea (ECS), indicating a close positive correlation between them. According to the extended record of altimetry-based sea level anomalies (SLAs) until 2020, however, the interannual variation of the Kuroshio intensity no longer has a strong positive correlation with eddy activity in the subtropical countercurrent (STCC) region since the early 2000s. Our observational analyses showed that the Kuroshio intensity in the ECS can be modulated by the combined effect of westward-migrating mesoscale eddies and westward-propagating oceanic planetary waves from the east. Until the early 2000s, the interannual variability of Kuroshio was mainly affected by eddy migration from the STCC region, associated with oceanic instability driven by large-scale wind patterns over the western North Pacific. Since then, oceanic planetary waves propagating westward across the Pacific basin have largely modulated the interannual variability of the ECS-Kuroshio intensity by superimposing the SLAs related to mesoscale eddies that propagated towards the east of Taiwan.